Preparing Schools and School Systems for the 21st Century - Withrow, Frank; Long, Harvey; Marx, Gary (Rowman & Littlefield Publishers, 1999)
This 112-page publication, Preparing Schools and School Systems for the 21st Century, presents characteristics of schools and school systems capable of preparing students for a global knowledge/information age. Order copies of this publication for board members, administrative team, staff, and community leaders. Use it to build support and stimulate discussions that will help you take leadership in reshaping your schools and school system for a new millennium. Characteristics of 21st century schools were identified by a distinguished council of 21 leaders in business, education, government and other fields during an historic Mount Vernon Conference. The council was under the honorary chairmanship of Senator John Glenn and was directed by the American Association of School Administrators. The study was made possible by financial support from AMP Incorporated and the Electric Power Research Institute.